Using phylogenetic diversity to identify ancient rain forest refugia and diversification zones in a biodiversity hotspot (2014)
Aim The plight of the world's biodiversity hotspots has been paralleled by a debate over how to best prioritize or maximize gain of biodiversity for conservation. Approaches to date have focused on quantifying species, habitat, phylogenetic or other types of diversity. The importance of preserving evolutionary distinctiveness or phylogenetic diversity (PD ) has gained popularity due to its ability to identify evolutionary patterns in the landscape that traditional taxon richness measures cannot. Here, we expand upon the application of PD as a biodiversity index and incorporate data on historical biogeography to understand the processes that shaped the assembly of a tropical flora. Location Tropical north?east Queensland, Australia. Methods We generated a genus?level molecular phylogeny for the bioregion to calculate PD . We then integrated data on historical biogeography into a model to explain the distribution of PD and the PD residuals and further tested for a correlation between rain forest stability through time and community assembly. Results We identified a strong correlation between PD residuals and the biogeographic origin of the lineages in the extant flora. Areas with higher PD than expected based on generic richness (GR ) contain a higher proportion of immigrant plant lineages dispersed into northern Australia mostly from Southeast Asia within the past few million years. Areas with lower PD than predicted by genus richness are rich in ancient Australian relict lineages and are correlated with previously identified rain forest refugia that have remained stable throughout the last glacial cycle. Main conclusions Maximizing PD without historical interpretation may yield unintended or undesirable conservation outcomes such as deprioritizing ancient refugia with lower PD values. By understanding the biome assembly of a region, better?informed decisions can be made to ensure different stages of a region's evolutionary history are preserved.